Consumer Perspectives on Digital Banking Solutions: Analyzing the Implementation of Digital Savings at PT Bank Rakyat Indonesia (Persero) - Syafitri, Eva Mirza; Subiyantoro, Subiyantoro; Azis, Aminudin; Syarifah, Ina (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2024)
PT Bank Rakyat Indonesia (Persero) Tbk. has introduced an innovative service, enabling customers to open savings accounts digitally, accessible anytime and anywhere without the need to visit the bank. The advent of this digital account opening system aims to enhance customer convenience through digital savings services. This study aims to assess customer perceptions regarding the quality of the product, service quality, emotional satisfaction, pricing, and costs associated with the digital savings account opening system at PT Bank Rakyat Indonesia (Persero) Tbk. KC Madun Unit Nglames. The research employs a descriptive quantitative methodology. Data sources include primary data from questionnaires completed by 35 respondents and secondary data from documentation on digital savings usage. The data are analyzed and discussed in relation to the theoretical framework, leading to a conclusion. The findings indicate that the digital savings account system is reasonably effective for account opening at PT Bank Rakyat Indonesia (Persero) Tbk. Madiun Branch Unit Nglames.